Outcome and Complications of MR Guided Focused Ultrasound for Essential Tremor: A Systematic Review and Meta-Analysis - Agrawal, Mohit; Garg, Kanwaljeet; Samala, Raghu; Rajan, Roopa; Naik, Vikas; Singh, Manmohan (Frontiers in Neurology, 2021)
Background: Magnetic resonance guided focused ultrasound (MRgFUS) is a relatively novel technique to treat essential tremor (ET). The objective of this review was to analyze the efficacy and the safety profile of MRgFUS for ET Methods: A systematic literature review was done. The post procedure changes in the Clinical Rating Scale for Tremor (CRST) score, hand score, disability and quality of life scores were analyzed. Results: We found 29 studies evaluating 617 patients. DTI based targeting was utilized in six cohorts. A significant difference was observed in the pooled standard mean difference between the pre and postoperative total CRST score (p-value <0.001 and 0.0002), hand score (p-value 0.03 and 0.02); and the disability at 12 months (p-value 0.01). Head pain and dizziness were the most in procedure complications. The immediate pooled proportion of ataxia was 50%, while it was 20% for sensory complications, which respectively declined to 31% and 13% on long term follow up. A significant reduction (p=0.03) in immediate ataxia related complications was seen with DTI targeting. Conclusion: MRgFUS for ET seems to be an effective procedure for relieving unilateral tremor. Some benefit of DTI based targeting in reducing immediate complications was observed but no significant effect on outcome could be established. Overall analysis of complications further revealed a decreasing trend on follow up.